2015
DOI: 10.1245/s10434-015-4552-x
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Lobular Carcinoma In Situ: Radiologic–Pathologic Features and Clinical Management

Abstract: Background Pleomorphic lobular carcinoma in situ (PLCIS) is an unusual variant of LCIS for which optimal management remains unclear. Methods We conducted a 15-year (2000–2014) retrospective chart review of the radiologic, pathologic, clinical management, and recurrence rates of patients with PLCIS on diagnostic biopsy. Fifty-one patients were found to have PLCIS either alone or with concomitant breast cancer. Of these, 23 were found to have pure PLCIS on diagnostic biopsy. Rates of upstaging after local exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 24 publications
2
25
0
4
Order By: Relevance
“…This is the position of the National Cancer Comprehensive Network (NCCN) and NHS breast screening program (NHSBSP) who recommend treating PLCIS similar to DCIS (29,30). However, as evident in more recent studies, such an approach may not be consistent with breast conservation (28). This clinical issue warrants investigation in appropriately powered, well-designed, prospective studies for a satisfactory resolution of all concerns.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the position of the National Cancer Comprehensive Network (NCCN) and NHS breast screening program (NHSBSP) who recommend treating PLCIS similar to DCIS (29,30). However, as evident in more recent studies, such an approach may not be consistent with breast conservation (28). This clinical issue warrants investigation in appropriately powered, well-designed, prospective studies for a satisfactory resolution of all concerns.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent study to comment on recurrence rates was that of Flanagan et al (28) who reported on a case series of 23 patients who were diagnosed with PLCIS. Of these 23 patients, 2 had adequate margins on the excisional biopsy and required no further intervention, while 16 underwent wide local excision and 5 had mastectomies.…”
Section: The Effect Of Surgical Margins and Adjuvant Therapy On Recurmentioning
confidence: 99%
See 2 more Smart Citations
“…Однако убе-дительных достоверных доказательств, что позитивные края при плеоморфном варианте LCIS существенно увеличивают риск рецидива, пока явно недостаточно. В отличие от классического варианта LCIS при плео-морфном варианте необходимо выполнять оперативное вмешательство (по крайней мере эксцизионную биоп-сию), так как более чем в 50 % (0-65 %) случаев в об-ласти первичной биопсии обнаруживается DCIS или инвазивный рак, которые и будут определять про-гноз заболевания [26]. При этом примерно в половине случаев приходится проводить мастэктомию, так как при таком варианте рака in situ сложно, а иногда и невозможно достичь негативных хирургических кра-ев из-за диффузного роста опухоли и мультифокально-сти (в том числе в виде очагов инвазивного рака).…”
Section: клинические рекомендацииunclassified